فاعلية استخدام الخرائط الذهنية الإلكترونية لتعليم مقرر مبادئ الاتصال بالجماهير لدى طلاب قسم الإعلام التربوي بكلية التربية النوعية جامعة بورسعيد - العميري، أحمد محمد صالح (جامعة القاهرة - كلية الإعلام, 2020)
تهدف الدراسة إلى قياس فاعلية استخدام الخرائط الذهنية الإلكترونية لتعليم مقرر مبادئ الاتصال بالجماهير لدى طلاب قسم الإعلام التربوي بكلية التربية النوعية جامعة بورسعيد، اعتمدت الدراسة على عينة عمدية بلغ عددها (44) طالبا من طلاب الفرقة الأولى بقسم الإعلام التربوي بكلية التربية النوعية جامعة بورسعيد والتي تتراوح أعمارهم ما بين (18-19) سنة من الذين يدرسون مقرر مبادئ الاتصال بالجماهير، وقد استخدم الباحث المنهج التجريبي وقد توصلت الدراسة إلى العديد من النتائج منها ثبت وجود فروق دالة إحصائيا بين القياسين القبلي والبعدي للمجموعة التجريبية لتعليم مقرر مبادئ الاتصال بالجماهير باستخدام الخرائط الذهنية الإلكترونية لدى طلاب الفرقة الأولى بقسم الإعلام التربوي لصالح القياس البعدي، كما أثبت وجود فروق دالة إحصائيا في القياس البعدي بين المجموعتين الضابطة والتجريبية لتعليم مقرر مبادئ الاتصال بالجماهير لدى طلاب الفرقة الأولى بقسم الإعلام التربوي لصالح المجموعة التجريبية.
The study aims to measure The effectiveness of using electronic mind maps to teach the basics mass communication course among the students of Educational Media Department at the Faculty of Specific Education Port Said University. The study relied on an intentional sample of (44) students from the first year in the Department of Educational Media at the Faculty of Specific Education, Port Said University, whose ages ranged between (18-19) years of those studying the basics mass communication course. The researcher used the experimental method. The study reached To many results, including it was proven that there are statistically significant differences between the pre and post measurements of the experimental group to teach the basics mass communication course using electronic maps for students of the first year in the Educational Media Department in favor of the post measurement, and it was also proven that there are statistically significant differences in the post measurement between the control and experimental groups to teach the basics mass communication course of the first year students in the Educational Media Department for the benefit of the experimental group.
Keywords: الإعلام التربوي -- المؤسسات التربوية -- الخرائط الذهنية الإلكترونية